Odpowiedzi

2009-12-11T19:43:18+01:00
A)
5x-y=1,5 /*6
3x+6y=4,2

30x-6y=9
3x+6y=4,2

33x=13,2 /:33
x=0,4

5x-y=1,5
5*0,4-y=1,5
2-y=1,5
-y=1,5-2
-y=-0,5 /*(-1)
y=0,5
b)
6x+2y=7 /*2
9x-4y=0

12x+4y=14
9x-4y=0
21x=14 /:21
x=14/21

9x-4y=0
9*14/21 -4y=0
126/21 - 4y=0
6-4y=0
-4y=-6 /:(-4)
y=1,5
c)
x+4y=1 /*2
x-8y= -1

2x+8y=2
x-8y=-1

3x=1 /:3
x=1/3

x-8y=-1
1/3-8y=-1
-8y=-1-1/3
-8y=-1 1/3
-8y=-4/3 /:(-8)
y=-4/3 * (- 1/8)
y=4/24
y=1/6
d)
5e-2f=8
-5e+f= -9
-f=-1 /*(-1)
f=1

5e-2f=8
5e-2*1=8
5e-2=8
5e=6 /:5
e=6/5
e=1,2

Pozdrawiam:)
2009-12-11T19:47:08+01:00
5x-y=1,5 / 6
3x+6y=4,2

30x-6y=9
3x+6y=4,2 +
-----------------

33x=13,2
x=0,4


2-y=1,5
x=0,4

x=0,4
-y=-0,5 / (-1)

x=0,4
y=0,5



---------------
6x+2y=7
9x-4y=0

6x+2y=7 / 2
9x-4y=0

12x+4y=14
9x-4y=0 +
------------------
21x=14
x=14/21
y=1,5




-------------------

x+4y=1
x-8y= -1 / (-1)

x+4y=1
-x+8y=1

12y=2
y=⅙

y=⅙
x+4⅙=1

y=⅙
x=-3⅙


------------------
5e-2f=8
-5e+f= -9 +
---------------

-f=-1 / (-1)
f=1

5e-2=8
f=1

f=1
5e=10/5

f=1
e=2
2009-12-11T19:54:21+01:00
1)
5x-y=1,5 / *6
3x+6y=4,2

30x-6y=9
3x+6y=4,2

33x= 13,2 /: 33
x=0,4

3x+6y=4,2
x=0,4

1,2+6y=4,2
x=0,4


6y=3 /:6
x=0,4

y = 0,5
x= 0,4

2)
6x+2y=7 /*2
9x-4y=0

12x+4y=14
9x-4y=0

21x=14 / :21
x= 2/3

12x+4y=14
x=2/3

8+4y=14
x=2/3

4y= 6 /:4
x=2/3

y = 1,5
x = 2/3

3)
x+4y=1 / * -1
x-8y= -1

-x-4y=-1
x-8y=-1

-4y=-2 / : -4
y= 0,5

x+4y=1
y=0,5

x+2=1
y=0,5

x=-1
y=0,5

4)
5e-2f=8
-5e+f= -9

-f=-1/: -1
f=1

5e-2f=8
f=1

5e-2=8
f=1

5e=10 /:5
f=1

e=2
f=1